Sally Ride - Orr, Tamra (New York, NY, 2004)
A biography of Sally Ride, discussing her early years, education, and career as one of the first women accepted in America's space program.
Includes bibliographical references and index.
Keywords: Juvenile literature; Ride, Sally; Astronauts; Biography; United States; Women astronauts; Biography; United States